Effect of Surfactants on Gas Holdup in Shear-Thinning Fluids - Shaobai Li; Siyuan Huang; Jungeng Fan (International Journal of Chemical Engineering)
In this study, the gas holdup of bubble swarms in shear-thinning fluids was experimentally studied at superficial gas velocities ranging from 0.001 to 0.02 m·s−1. Carboxylmethyl cellulose (CMC) solutions of 0.2 wt%, 0.6 wt%, and 1.0 wt% with sodium dodecyl sulfate (SDS) as the surfactant were used as the power-law (liquid phase), and nitrogen was used as the gas phase. Effects of SDS concentration, rheological behavior, and physical properties of the liquid phase and superficial gas velocity on gas holdup were investigated. Results indicated that gas holdup increases with increasing superficial gas velocity and decreasing CMC concentration. Moreover, the addition of SDS in CMC solutions increased gas holdup, and the degree increased with the surfactant concentration. An empirical correlation was proposed for evaluating gas holdup as a function of liquid surface tension, density, effective viscosity, rheological property, superficial gas velocity, and geometric characteristics of bubble columns using the experimental data obtained for the different superficial gas velocities and CMC solution concentrations with different surfactant solutions. These proposed correlations reasonably fitted the experimental data obtained for gas holdup in this system.